Wicked and wise: how to solve the world`s toughest problems - "Watkins, Alan & Wilber, Ken" (Kent, 2015)
Wicked and Wise : How to Solve the World$1 (Bs Toughest Problems is the first compelling title in a brand new series launching with Urbane Publications. A groundbreaking new series developed by leading consultant Alan Watkins, the Wicked and Wise explores a number of hotly debated and (3z(Bwicked(3y (Bissues facing the planet and its people, and offers some intelligent, challenging and (3z(Bwise(3y (Bways forward that may be able to break through the current intractable position. Each book in the series is co-authored by leading leadership consultant Alan Watkins and a hand-picked expert in each subject field. The first book in the series looks at some of the most pressing and topical issues affecting the world today, from the clash of religions and cultures in a globalised world to the growing dominance of technology. Co-written with renowned social thinker and philosopher Ken Wilber the book sets the scene for debating the key challenges facing current and future generations, and sets possible agendas for how leaders, and potential leaders, can solve challenges through the wise application of multi-tiered multi-channel, multi-organisational intervention and lead in a highly developed, enlightened & selfless way. s